Anticancer drug discovery by targeting cullin neddylation - Qing Yu; Yihan Jiang; Yi Sun (Elsevier, 2020)
Protein neddylation is a post-translational modification which transfers the ubiquitin-like protein NEDD8 to a lysine residue of the target substrate through a three-step enzymatic cascade. The best-known substrates of neddylation are cullin family proteins, which are the core component of Cullin-RING E3 ubiquitin ligases (CRLs). Given that cullin neddylation is required for CRL activity, and CRLs control the turn-over of a variety of key signal proteins and are often abnormally activated in cancers, targeting neddylation becomes a promising approach for discovery of novel anti-cancer therapeutics. In the past decade, we have witnessed significant progress in the field of protein neddylation from preclinical target validation, to drug screening, then to the clinical trials of neddylation inhibitors. In this review, we first briefly introduced the nature of protein neddylation and the regulation of neddylation cascade, followed by a summary of all reported chemical inhibitors of neddylation enzymes. We then discussed the structure-based targeting of protein-protein interaction in neddylation cascade, and finally the available approaches for the discovery of new neddylation inhibitors. This review will provide a focused, up-to-date and yet comprehensive overview on the discovery effort of neddylation inhibitors.